The Paraguayan economy growing and excludes. Implications for Labor Market - Ana Teresa Rojas Viñales (Población y Desarrollo, 2016)
Paraguay following the same economic path Latin America has had significant growth in the last 20 years; levels of poverty and inequality continue to show significant differences in the situation of the population and income redistribution. The Paraguayan economy based on the primary sector, mainly depends on weather conditions and international prices. Despite the country’s strategic position in international trade, the products are exported without processing. The country would receive better prices and higher incomes with the manufacture of the exported products. Participation rates in the labor market show greater male participation. The workers’ activities occur mainly in small businesses; the category of occupation concentrated Paraguayan workers is “self-employed”. Working conditions are different for men and women, as well as for people in urban and rural areas. Indicators of informality and precarious, show that, despite economic growth, labor market conditions continue to show weaknesses and the need to promote economic and social policies that generate higher investment in both human capital and productive infrastructure. Another important point that affects the labor market is the concentration of resources. In this sense, the concentration of land is one of the main pillars marking the path of the economy and income distribution.